1984
DOI: 10.1203/00006450-198409000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Growth-related Changes in Oxygen Uptake and Heart Rate during Progressive Exercise in Children

Abstract: SummaryAlthough body size and muscle mass increase considerably during growth in children, certain aerobic responses to exercise appear to be regulated so that the delivery of oxygen to muscle is maintained at optimized levels. We proposed that the relationship between oxygen uptake, (Voz) and heart rate (HR) was one of the regulated responses. We further hypothesized that the increase in Vo2 per increase in HR during progressive exercise would differ in subjects of different size, but when normalized to body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 13 publications
(6 reference statements)
5
53
0
2
Order By: Relevance
“…Also, PaCO2 seems to be controlled at lower levels in children compared to adults. These observations were corroborated indirectly by the measurements of end-tidal PCO2 (PETCO2) and showed that pre-exercise and peak-exercise values were signifi cantly lower in children as compared with PETCO2 in adults (23,27,28). Results showed that younger children breathed more during exercise to eliminate a given amount of CO2 to keep PaCO2 set point slightly but signifi cantly lower than older children or adults.…”
Section: Figuresupporting
confidence: 66%
See 1 more Smart Citation
“…Also, PaCO2 seems to be controlled at lower levels in children compared to adults. These observations were corroborated indirectly by the measurements of end-tidal PCO2 (PETCO2) and showed that pre-exercise and peak-exercise values were signifi cantly lower in children as compared with PETCO2 in adults (23,27,28). Results showed that younger children breathed more during exercise to eliminate a given amount of CO2 to keep PaCO2 set point slightly but signifi cantly lower than older children or adults.…”
Section: Figuresupporting
confidence: 66%
“…According to Fick principle, O2 pulse correlates with stroke volume. According to Cooper et al (23,24), we used end-tidal CO2 (PETCO2) to estimate PaCO2. Statistical analysis was performed with SPSS 11.5 (SPSS, Inc., Chicago, Illinois, USA).…”
Section: Methodsmentioning
confidence: 99%
“…COOPER et al [19] extensively studied such relationships in children and showed that the value of the slope during exercise was principally affected by weight (presumably reflecting muscular mass). Thus, the slope of V 'O 2 /fC normalized for differences in weight is independent of age [19]. In the present study, all values of the V 'O 2 /fC slope were within normal limits (mean± 2SD), or elevated in children.…”
Section: Discussionmentioning
confidence: 99%
“…3) and the ventilatory threshold tended to be lower in affected adult patients than in children. The slope of the V 'O 2 /fC relationship is an additional indicator of systolic ejection function during exercise [15,19]. A low slope of V 'O 2 /fC indicates that a high fC increase is associated with a given increase in V 'O 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Gas exchange was measured breathby-breath, 13 and the peak VO 2 was determined as previously described in children and adolescents. 14,15 Scaling ®tness to body size…”
Section: Fitness Assessmentmentioning
confidence: 99%